2017
DOI: 10.1007/s10995-017-2363-3
|View full text |Cite
|
Sign up to set email alerts
|

Illness Representations of Pertussis and Predictors of Child Vaccination Among Mothers in a Strict Vaccination Exemption State

Abstract: Background Vaccine preventable diseases are making a comeback in the US. However, research is lacking on illness representations of vaccine preventable diseases and their application in improving childhood immunization. Objective We utilized the common sense model of self-regulation to examine illness representations of pertussis and their associations with child's receipt of any vaccine, up-to-date vaccination status, and mothers' intentions to follow the recommended vaccination schedule in the future. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…This is an important area that needs to be addressed. This may hamper the routine process of vaccination for children and a resultant rise in infectious diseases 18. Another important misconception about children with ASD was that they do not show social attachment even to parents.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important area that needs to be addressed. This may hamper the routine process of vaccination for children and a resultant rise in infectious diseases 18. Another important misconception about children with ASD was that they do not show social attachment even to parents.…”
Section: Discussionmentioning
confidence: 99%
“…The better the illness perception is, the better the adherence. Mothers' beliefs about the benefits and side effects of vaccination have a greater influence than access to vaccinations on immunization behavior, which highlights the importance of parental perceptions of an illness and its management . Additionally, the emotional responses of patients can be affected by beliefs about an illness's etiology …”
Section: Discussionmentioning
confidence: 99%
“…Previous empirical studies showed that various illness representation dimensions are significantly associated with illness preventive behaviors, including vaccination. Particularly, perceptions of more severe consequences and possibilities for prevention, more concerns and worries about the illness, and a better understanding of the illness were positively related to the intention to and the actual engagement in preventive behaviors [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Neto and colleagues [ 44 ] investigated the associations of illness representations about COVID-19 with non-pharmacological preventive behaviors and found that more concerns about COVID-19 and more perceived personal control about COVID-19 were related to more social distancing, handwashing, and self-isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Former empirical studies found evidence that both dimensions of treatment perceptions are significantly related to the uptake of and adherence to pharmaceuticals, including vaccination. In particular, stronger perceptions of necessity and fewer concerns are associated with higher intentions to and actual higher levels of medication/vaccination uptake and adherence [ 34 , 37 , 39 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%